Paracoccus broussonetiae subsp. drimophilus subsp. nov., a Novel Subspecies Salt-Tolerant Endophytic Bacterium from Maize Root in Hunan - Xue Li; Chi Zhou; Ming Li; Qingzhuang Zhang; Lei Su; Xin Li (Life)
In an investigation exploring endophytic microbiota from agricultural crops, an aerobic, non-motile, Gram-negative, coccobacillus-shaped bacterial isolate, designated as strain NGMCC 1.201697T, was isolated from maize roots in Hunan Province, China. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain NGMCC 1.201697T belonged to the genus Paracoccus, showing the highest sequence similarity to Paracoccus broussonetiae CPCC 101403T (99.86%). The average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) were 98.57% and 87.90% between the novel isolate and its closest phylogenetic relative. However, phenotypic characterization further differentiated the isolate from P. broussonetiae CPCC 101403T. The isolate showed enhanced environmental tolerance adaptability (growth in 0–8% NaCl and 4–37 °C), unique enzymatic activities (esterase C4, β-glucosidase, L-proline arylamidase, and β-galactosidase), and expanded metabolic capabilities (D-mannitol, D-cellobiose, saccharose, and so on). The major polar lipids consisted of diphosphatidylglycerol (DPG), phosphatidylethanolamine (PE), phosphatidylcholine (PC), phosphatidylglycerol (PG), two unidentified glycolipids (GLs) and four unidentified phospholipids (PLs). The predominant respiratory quinone was ubiquinone-10, and the major fatty acid was summed feature 8 (C18:1 ω7c, 69.42%). The DNA G + C content was 64.49 mol%. Based on results of these analyses, strain NGMCC 1.201697T represents a novel subspecies of Paracoccus broussonetiae, for which the name Paracoccus broussonetiae subsp. drimophilus subsp. nov. is proposed. The type-strain is NGMCC 1.201697T (=CGMCC 1.61958T =JCM 37104T).